2022
DOI: 10.30935/cedtech/11541
|View full text |Cite
|
Sign up to set email alerts
|

Saudi Arabia Special Education Teachers’ Attitudes Toward Assistive Technology Use For Students With Intellectual Disability

Abstract: This study was conducted in the central region of the Kingdom of Saudi Arabia (KSA) to investigate levels of teachers' assistive technology (AT) knowledge and skills use in classrooms for students with intellectual disability (ID). A total of 98 special education teachers of students with ID completed an online survey. Results indicate that the teachers' levels of knowledge and skills related to AT use in classrooms for students with ID were reaching proficiency. Teachers' levels of AT knowledge and skills sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
0
1

Year Published

2022
2022
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 16 publications
0
0
1
Order By: Relevance
“…Furthermore, the results for the level of education, years of teaching experience, and grade level taught variables in the current study revealed no statistically significant differences in these teachers' perspectives on the other three obstacles related to the tools used in educational rehabilitation, school administration and equipment, and SWID. These findings are important because they contrast with Aldehami's (2022) results indicating that the perspectives of teachers who had obtained higher academic degrees were significantly different from teachers who had obtained lower-level degrees. Researchers also explained that teachers who expressed sufficient levels of knowledge had enrolled in professional development programs or had taken college-level courses (Bell et al, 2010;Van Laarhoven & Conderman, 2011).…”
Section: Rq 3 4 Andcontrasting
confidence: 84%
“…Furthermore, the results for the level of education, years of teaching experience, and grade level taught variables in the current study revealed no statistically significant differences in these teachers' perspectives on the other three obstacles related to the tools used in educational rehabilitation, school administration and equipment, and SWID. These findings are important because they contrast with Aldehami's (2022) results indicating that the perspectives of teachers who had obtained higher academic degrees were significantly different from teachers who had obtained lower-level degrees. Researchers also explained that teachers who expressed sufficient levels of knowledge had enrolled in professional development programs or had taken college-level courses (Bell et al, 2010;Van Laarhoven & Conderman, 2011).…”
Section: Rq 3 4 Andcontrasting
confidence: 84%
“…In addition, there is an impact on the increased attention and focus of students in the classroom. The interaction and communication between students and teachers have also succeeded in creating an interesting and fun environment (Aldehami, 2022). The study successfully demonstrated that the Robot-Assisted Autism Therapy (RAAT) system developed provides accuracy in measuring the involvement of autism students during therapy in education.…”
Section: Methodsmentioning
confidence: 95%
“…Teachers understand the application of assistive technology for instructional purposes and acquiring knowledge within the classroom setting. Aldehami (2022) found that while most teachers possess fundamental understanding of assistive technology, their level of knowledge varies depending on the educational setting. The emphasis placed by the school plays a crucial role in ensuring that teachers possess comprehensive knowledge regarding the utilization of this assistive technology.…”
Section: Methodsmentioning
confidence: 99%
“…Analizom deskriptivnih postignuća uviđamo da oligofrenolozi iz uzorka imaju pozitivne stavove prema upotrebi AT u nastavi, što je u saglasnosti sa prethodnim istraživanjima (Aldehami, 2022;Kundu et al, 2020). Ispitanici iz uzorka smatraju da su u dovoljnoj meri kompetentni da primenjuju AT u svakodnevnoj nastavi.…”
Section: Diskusijaunclassified
“…Nisu utvrđene statistički značajne razlike između ispitanika u pogledu stavova prema primeni AT, motivacije za primenom AT, kao ni samopercepcije kompetencija, u odnosu na pol, najviši završeni stepen obrazovanja, godine radnog iskustva, i kategoriju dece sa kojom rade, kao ni pohađanje obuka o primeni AT u nastavi. Ovakvi nalazi su u saglasnosti sa prethodnim istraživanjima u kojima takođe nisu dobijene razlike između ispitanika u pogledu navedenih varijabli (Alasmari, 2020;Aldehami, 2022;Felicia, Sharif, Wong, & Marriappan, 2014;Lindeblad, Nilsson, Gustafson, & Svensson, 2017). Kada su u pitanju nalazi koji se odnose na pohađanje obuka o primeni AT, postoji veliki broj istraživanja koja ukazuju na to da proširivanje znanja iz oblasti AT (Aldehami, 2022), dovodi do veće želje i motivacije za primenom AT (Buehler et al, 2015;Young, 2012), a samim tim i do povećanja kompetencija u navedenoj oblasti (Onivehu et al, 2017).…”
Section: Diskusijaunclassified